Development of dehydrated langka-papaya fruit bar - Coran, Elizabeth R. (1979)
Langka-papaya fruit bars were developed by partial dehydration of the puree using the cabinet drier. Drying of puree with varying soluble solids content was done. Based on the results of the objective and sensory evaluations, the best langka-papaya fruit bar was produced from puree with a soluble solids content of 25°B. Drying of puree with the most acceptable soluble solids content of 25°B at four different time-temperature combinations was also done. Results of the objective and sensory evaluations revealed that the purees dried at 150°F for 3 hours were the best to produce.